The different roles of innate immune receptors in inflammation and carcinogenesis between races - Natsu Yamaguchi; Yoshimi Suzuki; M. H. Mahbub; Hidekazu Takahashi; Ryosuke Hase; Yasutaka Ishimaru; Hiroshi Sunagawa; Rie Watanabe; Yoshinobu Eishi; Tsuyoshi Tanabe (Komiyama Printing Co. Ltd, 2017)
Abstract Innate immune factors exert widespread effects on cytokine secretion, cell survival, autophagy, and apoptosis. Nucleotide-binding and oligomerization domain-like receptors (NLRs) are members of the innate immune system in the cytosol that sense pathogens, endogenous danger molecules such as uric acid, and pollutants. Nucleotide-binding oligomerization domain-containing protein 1 and 2 (NOD1 and NOD2) are components of NLR family, and ligands of these factors are γ-d-glutamyl-meso-diaminopimelic acid (iE-DAP) and muramyl dipeptide (MDP), respectively. Upon recognition of ligands, NOD1 and NOD2 induce the production of inflammatory cytokines and transcription factors including interleukin-6 (IL-6) and nuclear factor-κB (NF-κB). We examined the function of NOD1 and NOD2 in innate immunity, with a focus on their differing roles in disease pathogenesis between Japanese and Caucasian populations. Susceptibility to several immune-related diseases, including Crohn's disease, colorectal and breast cancers, and graft-versus-host-disease (GVHD) showed a correlation with genetic variants of NOD2 in Caucasian, but not in Japanese, populations. This difference may be primarily due to the fact that three major NOD2 SNPs (R702W, G908R, L1007insC) prevalent in Caucasians are rare or absent in Japanese populations. Because NLR has diverse effects on immune function, it is possible that many as yet uncharacterized immune-related diseases will also show different susceptibilities between races due to the different ratio of genetic variants in innate immune genes.